NASIONALISME DAN KESADARAN KETURUNAN ETNIS TIONGHOA DALAM MEMPERTAHANKAN IDENTITAS NASIONAL DI KALIMANTAN BARAT - Fernandez, Ivan; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is motivated by perceptions and assumptions in the community regarding the lack of awareness of Chinese ethnic nationalism in maintaining national identity in West Kalimantan. The purpose of this study is to clearly identify the facts regarding the awareness of nationalism of Chinese descent in national defense in West Kalimantan. This study uses a qualitative research method with a realist ethnographic approach. The data sources in this study were obtained from the Chairperson of the MABT DPP, the Chinese ethnic community, and the non-ethnic Chinese community in Kubu Raya Regency, West Kalimantan. Data was collected using interview techniques, field observations, interview guides and documentation tools. The results of data analysis in this study were presented in a qualitative descriptive manner using 9 informants. This study found the following facts: (1) Ethnic Chinese have a good awareness of nationalism with the establishment of the Chinese Cultural Customary Council (MABT) which works as a forum for Chinese ethnic groups to advance West Kalimantan. (2) Ethnic Chinese maintain national identity without losing their ethno-cultural identity (3) Ethnic Chinese are proven to be active in community activities and maintain tolerance between ethnicities, races and religions. (4) Awareness of ethnic Chinese descent, seen from the cognitive, affective and conative aspects, has a positive attitude towards Indonesian by introducing, improving and also frequently using Indonesian in Kalimantan Barat.